Aktivitas Dakwah Gerakan Salafi Pada Masa Pandemi Covid-19 - Jeudi Aneigia Branchais; Agus Machfud Fauzi (LPPM STAI Diniyah Pekanbaru, 2021)
Da'wah is an activity that is needed by Muslims, it is a means of conveying Islamic teachings. During the current COVID-19 (Coronavirus Disease) pandemic, da'wah activities have undergone a massive evolution in the public space. This condition is a challenge for da'I and mad'u. This implication is also experienced by followers of the salafi movement. The implementation of preaching, which was originally cultured face to face, changed to screen which massively demanded rapid adaptation. This study aims to explore the symptoms of the salafi da'wah phenomenon carried out online during the COVID-19 pandemic. Through a phenomenological approach, this study investigates pure symptoms that are independent of the intervention. Using qualitative methods, it is known that the salafi movement makes use of information technology in preaching activities. The salafi movement applies the concept of e-da'wah, namely using WhatsApp lectures, zoom, google meet, streaming youtube, podcast, clubhouse, Twitter, telegram, and others. Not only in the da'wah program, this activity is also carried out in the Al-Qur'an tahfidz program and joint charity.